MODIFIED WATER SPRAY CHUMMING SYSTEM FOR POLE AND LINE FISHING OF TUNA - NAMBOODIRI, K SREEDHARAN (Fishery Technology, 2017)
A water spray chumming system consisting of a 65 x 50 mm centrifugal pump driven by the propulsion engine through a PTO clutch and 'V' pulley power transmfasion system has been developed for the pole and line :fishing of tuna. Water is sprayed through pipe loop system fitted on the edge of the ,:fishing platform of the boat through smaU holes. The distance of the spray length can be adjusted by controlling the flow of the pump discharge water through a wheel valve.